Indicadores da resposta inflamatória sistêmica em coelhos (Oryctolagus cuniculus) infectados experimentalmente com oocistos esporulados de Eimeria stiedai (Apicomplexa: Eimeriidae) - da Costa Freitas, Fagner Luiz; Yamamoto, Beatriz Lie; da Costa Freitas, Wagner Luiz; Fagliari, Jose Jurandir [UNESP]; de Sousa Almeida, Katyane; Machado, Rosangela Zacarias [UNESP]; Machado, Celio Raimundo [UNESP] (My University, 2011)
Hemograms and acute-phase proteins in adult male New Zealand White rabbits that had been experimentally infected orally with sporulated oocysts of Eimeria stiedai were evaluated over a 28-day period. Fifty animals were used, divided into two groups: group A infected with 1 × 10 4 sporulated oocysts of E. stiedai and group B inoculated with distilled water. On the seventh day after infection, the infected animals presented anemia and leukocytosis with neutrophilia and monocytosis. Protein fractionation by means of electrophoresis identified 19 acute-phase proteins with molecular weights ranging from 24 to 238 kD. Ceruloplasmin, transferrin and haptoglobin showed high levels on the seventh day after infection, with gradual increases in their concentrations until the end of the experimental period. Thus, from the data of the present study, E. stiedai is considered to be a pyogenic etiological agent for which the infection level can be monitored through the leukocyte count and serum concentrations of ceruloplasmin, transferrin and haptoglobin, and these can be recommended as complementary tests.
Systemic inflammatory response indicators in rabbits (Oryctolagus cuniculus) experimentally infected with sporulated oocysts of Eimeria stiedai (Apicomplexa: Eimeriidae)
Keywords: Acute-phase proteins; Eimeria stiedai; Oryctolagus cuniculus